The Impact of Macroeconomic Variables and Political Events on the Jakarta Islamic Index - Yudi Chandra Harahap; Hikmah Endraswati; Ibnu Muhdir (Program Studi Magister Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Sunan Kalijaga, 2026)
The inconsistency of research findings regarding the influence of macroeconomic variables on the Islamic stock market, along with the increasing role of non-economic factors such as political events, indicates that the dynamics of the Jakarta Islamic Index (JII) cannot be fully explained solely by macroeconomic indicators. This study aims to analyze the effects of inflation, the rupiah exchange rate, the BI Rate, sectoral production indices (mining, manufacturing, and construction), foreign exchange reserves, and political events on the JII during the 2022–2024 period using monthly time-series data. This study employs a multiple linear regression model with the Efficient Market Hypothesis and Behavioral Finance as its theoretical foundations. The results indicate that the BI Rate and sectoral production indices have a positive and significant effect on the JII, while inflation, the exchange rate, and foreign exchange reserves do not have a significant effect. In addition, political events, proxied by the official certification of the presidential election results, are found to have a positive and significant effect on the JII. These findings suggest that non-economic factors play an important role in influencing the dynamics of the Islamic stock market. Therefore, market analysis should consider not only fundamental factors but also investor expectations and sentiment.